Strategi Pembelajaran KICI (Kolaboratif, Interaktif, Cerdas Digital, Integratif) untuk Meningkatkan Keterampilan Abad 21 Peserta Didik - Rezky Awalia; Muhiddin Palennari (STKIP Subang, 2025)
The demands of the industrial revolution 5.0 era require education to transform its focus from knowledge transfer to the formation of 21st Century Skills (4C: Critical Thinking, Creativity, Collaboration, and Communication)1. The existing facts in learning practices, especially Biology learning, are still dominated by teacher-centered methods which result in a lack of mastery of concepts by students. This article aims to develop a theoretical framework and syntax of the KICI learning strategy (Collaborative, Interactive, Digitally Intelligent, Integrative) as a holistic solution. The writing of this qualitative conceptual development article uses an in-depth literature study to synthesize the principles of Social Constructivism, Behavioristic Repetition, and Education for Sustainable Development (ESD). The result is the formulation of a KICI strategy consisting of four core pillars and six structured learning stages. Theoretically, the KICI strategy has significant potential in improving 21st Century Skills. The Collaborative pillar fosters teamwork and interpersonal communication. Digitally Intelligent facilitates creativity and multimodal communication through the use of interactive media and digital technology. Integrative encourages critical thinking and social responsibility by linking Biology to SDGs issues. Meanwhile, the Interactive pillar, which includes the Repetition & Feedback (RU) stage, serves to deepen mastery of Biology concepts through reflective practice. The KICI strategy offers novelty through a cohesive synthesis of these four pillars in a single, systematic syntax, bridging the Biology curriculum with global skill demands.